Injective and pejorative vocabulary in interpersonal conflict (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The paper identified features of using pejorative language and injective in interpersonal conflict interaction, which is represented in the works of S. Andrukhovych, I. Carp, T. Malyarchuk, M. Matios, S. Pyrkalo, I. Rozdobudko, M. Ryapolova, G. Tarasyuk. The role of pejorative language and injective as a special communicative tactics that affects the entire system of communication and mechanisms for its deployment, was analyzed.
Keywords: interpersonal conflict; pejorative vocabulary; vocabulary injective